Designing brazing filler metal for heat-resistant nickel alloys of new generation marine gas turbines - Kvasnytskyi, Viktor; Korzhyk, Volodymyr; Kvasnytskyi, Viacheslav; Matviienko, Maksym; Buturlia, Yevhen; Lahodzinskyi, Ivan (Eastern-European Journal of Enterprise Technologies, 2023)
The object of research is the processes of the formation of brazed joints and the stressed state. The subject of research is structure, chemical composition, long-term high-temperature strength at a temperature of 900 °C, speed of high-temperature salt corrosion. Existing brazing filler metals have a high-temperature performance of 40–50 % of the performance of the SM93-VI and SM96-VI alloys. Despite this, brazing is the main technique of joining modern heat-resistant cast alloys. Therefore, the development of new brazing filler metals that ensure the formation of joints with increased long-term high-temperature strength is relevant. Ship gas turbine blades operate at a temperature of 900 °C. The purpose of the development of the new SBM-4 brazing filler metal is to achieve long-term high-temperature strength of brazed joints at a temperature of 900 °C at the level of 85–90 % of the strength of heat-resistant alloys SM93-VI and SM96-VI. A two-stage method was used in the development of SBM-4 brazing filler metal. At the first stage, the chemical composition of the brazing filler metal base was determined, taking into account the peculiarities of operating conditions of the blades of marine gas turbine engines and the achievements of materials science of heat-resistant alloys. At the second stage, the depressant and its necessary content were selected. Computer software was used to determine the distribution between the γ- and γ'-phases, taking into account the participation of each element in both dispersion and solid-solution strengthening. Rational limits of concentrations of alloying elements were determined. The criterion was the minimum susceptibility of brazing filler metal to the formation of brittle phases, taking into account the influence of chromium, rhenium, and tantalum concentrations on resistance to high-temperature salt corrosion and high-temperature performance. The long-term strength of SM93-VI and CM96-VI alloys brazed with SBM-4 brazing filler metal is 89–91 % of the strength of the base metal. Technologies of brazing and correction of casting defects have been introduced into production.